Wady ludzi starych w ocenie Jana Chryzostoma - Szczur, Piotr (Vox Patrum, 2011)
From John Chrysostom’s writings – and especially his homilies – quite a picturesque portrait of old people emerges. Generally speaking, in this instance the golden-mouth preacher talks as a representative of early-Christian writers, who gave old people the privileged status. However, along with some praises for the elderly and old age we can also find his comments concerning faults of people of advanced age. Chrysostom talks about these faults especially while speaking about the great responsibility of the elderly for the upbringing of the young. Trying to stress their responsibility the Antiochene exaggerates their faults in order to motivate them to become models and to set an example to the young generation. In this context he judges old people’s disgraceful behaviour that involves surrendering to weaknesses typical of young age, frequenting hippodromes and theatres, giving bad example, lack of proper care about children’s upbringing, or even teaching the young some wrong ways. The consequence of such behaviour is that the old themselves contribute to the process of diminishing the value of ‘silver hair’ and lack of esteem the old demand from the young because of their advanced age.